TEMPORALITY AND OLD AGE PROLEGOMENE FOR AN EPILEGOMENE - TZITZIS, Stamatios (MEDECINE LEGALE DROIT MEDICAL, 2025)
Human existence is measured by its biological temporality. Old age marks the eternal return to a time when one arrives at the world alone without being asked and inexorably moves towards a solitary departure at an imprecise and unsolicited time, if the unexpected has not done its work in the meantime. One thing is certain, old age cannot be conceived outside its temporality, which guarantees the incessant movements of life. The ethics of old age is therefore situated in the experience of each person’s temporality. It is highly determined by individual psychology, which forms its existential philosophy. The subjective aspect of this ethic is at stake. Another aspect, the objective, is no less real. How do the state order and the societal order deal with old age? What existential value do these orders attribute to this natural state of man which makes him vulnerable? How does this concern translate into care and protection on the part of the authorities? So these are the fundamental points that we propose to develop in our work.